CTL‐associated and NK cell‐associated immune responses induce different HBV DNA reduction patterns in chronic hepatitis B patients. Issue 12 (29th August 2018) - Nomura, Motonobu; Tsuge, Masataka; Uchida, Takuro; Hiraga, Nobuhiko; Kurihara, Mio; Tsushima, Ken; Fujino, Hatsue; Nakahara, Takashi; Murakami, Eisuke; Abe‐Chayama, Hiromi; Kawaoka, Tomokazu; Miki, Daiki; et al.
Summary: The activation of hepatitis B virus (HBV)‐related hepatitis is associated with both natural killer (NK) cells and cytotoxic T lymphocytes (CTLs). We analyzed the association between the immune response and changes in the proportion of Pre‐S deletion variants. We quantified Pre‐S deleted HBV (HBV‐del) and wild‐type HBV (HBV‐wt) DNA levels in sera obtained from HBV‐infected mice and chronic hepatitis B patients. In chronic hepatitis B patients, the HBV‐del proportion usually increased during or after ALT elevation but did not occur during all ALT elevations. To clarify this difference in the immunological responses, we performed in vivo analyses using HBV‐infected human hepatocyte chimeric mice. Although HBV‐del proportions did not change in mice with NK cell‐associated hepatitis or in mice treated with entecavir, the proportions sharply increased in mice with CTL‐associated hepatitis. Furthermore, the number of patients in which HBV‐del proportions were greater than 5% was significantly higher in chronic hepatitis B patients than in asymptomatic carriers ( P  = 0.023). We identified associations between virological response in chronic hepatitis B patients and two different immune responses. The proportion of HBV‐del variants could be a useful biomarker for distinguishing between chronic hepatitis and asymptomatic carriers.